2023
DOI: 10.55493/5002.v13i3.4758
|View full text |Cite
|
Sign up to set email alerts
|

Does foreign direct investment affect poverty in BRICS?

Abstract: This study examined the influence of foreign direct investment (FDI) on poverty alleviation in BRICS countries (Brazil, Russia, India, China, and South Africa) using panel methods of econometric estimation, namely pooled ordinary least squares (OLS), fixed effects and fully modified ordinary least squares (FMOLS). Data from 1989 to 2020 was used in this study. The majority of research on FDI-led poverty has ignored the omitted variable bias. Economic growth as a channel in the FDI–poverty nexus was also explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
0
1
Order By: Relevance
“…It should be noted, according to the results of our estimates, that there is no significant impact between FDI and domestic investment GCF on extreme poverty in both regimes. Our findings regarding the relationship between FDI and poverty reduction are in opposition to those obtained by Tsaurai (2023), Algan et al (2021), Topalli et al (2021), Ahmad et al (2019), Ngo (2019), Tsaurai (2018), Fowowe andShuaibu (2014), andJalilian andWeiss (2002), who showed that FDI contributes positively and significantly to poverty reduction. Also, our results are not consistent with those obtained by Bornschier and Chase-Dunn (1985), who found that FDI exacerbates poverty.…”
Section: Dynamic Panel Threshold Estimationcontrasting
confidence: 99%
“…It should be noted, according to the results of our estimates, that there is no significant impact between FDI and domestic investment GCF on extreme poverty in both regimes. Our findings regarding the relationship between FDI and poverty reduction are in opposition to those obtained by Tsaurai (2023), Algan et al (2021), Topalli et al (2021), Ahmad et al (2019), Ngo (2019), Tsaurai (2018), Fowowe andShuaibu (2014), andJalilian andWeiss (2002), who showed that FDI contributes positively and significantly to poverty reduction. Also, our results are not consistent with those obtained by Bornschier and Chase-Dunn (1985), who found that FDI exacerbates poverty.…”
Section: Dynamic Panel Threshold Estimationcontrasting
confidence: 99%